2021
DOI: 10.1186/s40359-021-00701-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the mental health and wellbeing of parents with young children: a qualitative interview study

Abstract: Background Parents have faced unique challenges during the coronavirus disease 2019 (COVID-19) pandemic, including mobility constraints, isolation measures, working from home, and the closure of schools and childcare facilities. There is presently a lack of in-depth qualitative research exploring how these changes have affected parents’ mental health and wellbeing. Methods Semi-structured qualitative interviews with 29 parents of young children. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 37 publications
(28 reference statements)
6
46
0
2
Order By: Relevance
“…This has been reported previously 21,22 , as have the challenges of balancing personal and professional stressors. For example, home working was experienced positively by some, providing time to slow down and connect with family, but others reported this to have been a negative experience, with social isolation, home schooling while trying to work, and physical health impacts all issues of concern 31,32 .…”
Section: Results In Relation To Previous Researchmentioning
confidence: 99%
“…This has been reported previously 21,22 , as have the challenges of balancing personal and professional stressors. For example, home working was experienced positively by some, providing time to slow down and connect with family, but others reported this to have been a negative experience, with social isolation, home schooling while trying to work, and physical health impacts all issues of concern 31,32 .…”
Section: Results In Relation To Previous Researchmentioning
confidence: 99%
“…They interviewed 549 families with 1098 children (two per family) aged 5-18 years old, and showed that stress related to COVID-19 corresponded to greater differences in the mental health of the siblings; specifically, the sibling with poorer mental health received lowerquality parenting over the study period, such as in terms of less attention. Dawes et al (2021) also reported particular stress factors experienced by parents of children aged 0-12 years during the COVID-19 pandemic in the UK [38]. Their results highlighted the difficulty of coping with various household tasks and adapting the previous structures and routines of home life to the new situation.…”
Section: Discussionmentioning
confidence: 99%
“…Interviewers were male and female postgraduate researchers who had prior experience of conducting qualitative interviews with people experiencing physical and mental health difficulties, and vulnerable groups. Interviews followed a topic guide designed to explore the impact of the pandemic on participants’ mental health, social lives and worries for the future, the findings of which have been published [ 40 , 41 , 42 , 43 , 44 ]. No formal piloting of the interview schedule took place, as it was deemed important for the study to commence as soon as possible to capture early experiences of the pandemic.…”
Section: Methodsmentioning
confidence: 99%